Perencanaan Strategik Kurikulum Adaptif Untuk Pembelajaran Mendalam Dalam Kurikulum Merdeka - Novia Indriyani; Renny Fijarwati; Rukmosari Handayani; Ngurah Ayu Nyoman (Universitas Muhammadiyah Bangka Belitung, 2026)
This study aims to understand the strategic planning of the Adaptive Curriculum and its contribution to the implementation of Deep Learning within the Merdeka Curriculum. The study emphasizes the importance of aligning strategic vision, teacher readiness, supportive learning environments, and sustainable monitoring and evaluation mechanisms. A literature review method was employed to analyze the concepts of the Adaptive Curriculum, Deep Learning, and their implementation practices in educational institutions. The findings indicate that the Merdeka Curriculum is designed to be adaptive, emphasizing flexibility in learning pathways, pacing, and content, while supporting the development of the Pancasila Student Profile through conscious, meaningful, and engaging learning experiences. However, implementation in the field faces operational capacity gaps, including limited teacher competencies in differentiation and Deep Learning, disparities in digital and physical infrastructure, and budget allocations that do not fully support intensive training. Strategic school leadership has proven to be a key factor in managing resources, facilitating curriculum adoption, and leading collaborative change strategies. Long-term monitoring and evaluation mechanisms, based on the CIPP Model, assess the quality of adaptive instruction processes, interactive activities, student intrinsic motivation, and character development, allowing for dynamic and responsive curriculum adjustments. In conclusion, strategic planning of the Adaptive Curriculum is a crucial foundation for relevant, flexible, and sustainable learning. Effective implementation requires inclusive leadership, teacher capacity development, stakeholder collaboration, and holistic evaluation mechanisms to ensure the Merdeka Curriculum remains adaptive and responsive to student needs and contemporary educational challenges